Lithiated VO2(M)@Carbon Fibers Hybrid Host for Improving the Cycling Stability of Sulfur Cathode in Lithium‐Sulfur Batteries†. Issue 12 (17th November 2020) - Wang, Yuxin; Zhang, Ling; Bi, Jiaying; Yang, Hao; Zhao, Zhikun; Mu, Daobin; Wu, Borong
Summary of main observation and conclusion: We successfully prepared the Li‐VO2 (M) nanosheets via a facile lithiation method. After compositing with conductive carbon fibers, the sulfur host (Li‐VO2 (M)@CFs) combines the efficient adsorption ability of the VO2 (M) with superior electronic conductivity of the carbon fibers. Besides, carbon fiber cloth used as the current collector can provide the 3D electronic channels. Therefore, the coin cells exhibited the superior reversible capacity of 1250 mA h g –1 at 0.2 C and a low capacity decay value of 0.068% per cycle within 416 cycles at 1 C, indicative of the favorable cycling stability. Moreover, even at a high rate of 5 C, it also kept at a high discharge capacity of 401 mA h g –1 . In conclusion, this work discloses an attractive route to reduce the dissolution loss of lithium polysulfides (LiPSs) and enhance the overall performance of Li‐S batteries. Abstract : This work discloses an attractive route to reduce the dissolution loss of lithium polysulfides (LiPSs) and enhance the overall performance of Li‐S batteries.